A shared hosting platform model and the vector packing problem to resource allocation for virtual service - Ban, Đoàn Văn; Nhật, Phạm Minh; Sơn, Lê Văn (Journal of Computer Science and Cybernetics, 2014)
In cloud computing, optimizing resource for virtual services to enhance IaaS service performance and meet the requirements of efficient resource exploitation is an attractive issue in recent times. In this paper, we study the problem of providing multi-dimensional resources based on shared hosting platforms for virtual services. We construct the problem as an optimization formulation that uses a linear programming to minimize the number of physical servers. The solution to this formulation is applying the standard algorithms of vector packing problem to solve and evaluate solutions via emulation-based program.